Avatar-based therapy within prison settings: pilot evaluation. Issue 3 (27th May 2017) - van Rijn, Biljana; Cooper, Mick; Jackson, Andrew; Wild, Ciara
ABSTRACT: The paper presents an introduction of a newly developed, avatar-based virtual reality therapy, as an addition to the therapeutic programme, within a therapeutic community prison in the UK. The participants had six group sessions facilitated by a counsellor. The aim of the project was to investigate whether this approach would improve mental health outcomes for the prisoners, interpersonal relationships within the prison and facilitate the achievement of personal goals for the prisoners. The sample size ( n = 4) was insufficient to make firm conclusions about the mental health outcomes. However, the qualitative analysis showed a strong engagement with the programme in addressing personal issues, the development of insight and empathy, and improvements in relationships within the participants and with the counsellor. Further research with a larger sample is needed to establish efficacy of this type of therapy with the prison population.